Breakneck - Cameron, Marc (Cameron, Marc. Arliss Cutter novel., 2023)
"In Washington, DC, Supreme Court Justice Charlotte Morehouse prepares for a trip to Alaska, unaware that a killer is waiting to take his revenge--by livestreaming her death to the world. In Anchorage, Alaska, Deputy US Marshals Arliss Cutter and Lola Teariki are assigned to security detail at a judicial conference in Fairbanks. Lola is tasked with guarding Justice Townsend's teenaged daughter while Cutter provides counter-surveillance. It's a simple, routine assignment--until the mother and daughter decide to explore the Alaskan wilderness on the famous Glacier Discovery train. Hiding onboard are Chechen terrorists, who launch a surprise attack. While they seize control of the engine, Cutter manages to escape with Justice Townsend by jumping off the moving train--and into the unforgiving wilderness. With no supplies and no connection to the outside world, Cutter and the judge must cross a treacherous terrain to stay alive. Two of the terrorists are close behind. The others are on the train with the judge's daughter--and they plan to execute her on camera. With so many lives at stake, Cutter knows there are only two options left: catch the train and kill them all ... or all will be killed"--